Psychological burden in female caregivers of patients with dementia and associated behavioral and emotional problems, during COVID-19 pandemic restrictions - Σοπίδου, Κυριακή; Μωραΐτου, Δέσποινα; Τσολάκη, Μαγδαληνή; Παπαντωνίου, Γεωργία (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2024)
This study explores the impact of the COVID-19 pandemic on female caregivers of dementia patients, delving into their experiences before and after the pandemic. Contrary to expectations, the findings reveal that caregiver burden did not significantly increase post-pandemic. The study focuses on Greek female caregivers of dementia patients with behavioral and psychological symptoms associated with neurocognitive disorders, navigating the intersection of the pandemic and the ongoing challenge of dementia, emphasizing the vulnerability of older adults with dementia during COVID-19. Specifically, the study investigates the psychological burden on female caregivers, often spouses or daughters, and explores the relationship between caregiver burden and death anxiety. Surprisingly, the results show no significant correlation between caregiver burden and death anxiety during the pandemic. The study underscores the need for additional support strategies for caregivers and emphasizes the importance of considering diverse cultural contexts in understanding caregiving experiences during crises. Overall, the research contributes valuable insights into the complex dynamics faced by female caregivers in the context of dementia and the COVID-19 pandemic.